Recent advantages in laser fabrication of micro-channel heat exchangers: Fortschritte in der Herstellung von Mikrokanal Wärmetauschern mittels Laserherstellung - Mehrpouya, M. (Wiley-VCH Verlag, 2017)
Micro-channel heat exchangers transfer more heat because of having a greater surface area compared to the conventional generation. This principle advantage can be applied widely in various industries for waste heat recovery purposes. Laser micromachining is a unique fabrication process, which presents some challenges. The main drawback of laser processes is introduction of residual stresses, which create distortion on the surface of heat-affected areas. This study investigates some recent improvement in the fabrication methods of micro-channel heat exchangers and concludes the strategies to control the distortion. © 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim